Holocene earthquake history and slip rate of the southern Teton fault, Wyoming, USAAbstract - DuRoss, Christopher B.; Gold, Ryan D.; Briggs, Richard W.; Delano, Jaime E.; Ostenaa, Dean A.; Zellman, Mark S.; Cholewinski, Nicole; Wittke, Seth J.; Mahan, Shannon A. (GSA Bulletin, 2020)
The 72-km-long Teton normal fault bounds the eastern base of the Teton Range in northwestern Wyoming, USA. Although geomorphic surfaces along the fault record latest Pleistocene to Holocene fault movement, the postglacial earthquake history of the fault has remained enigmatic. We excavated a paleoseismic trench at the Buffalo Bowl site along the southernmost part of the fault to determine its Holocene rupture history and slip rate. At the site, ∼6.3 m of displacement postdates an early Holocene (ca. 10.5 ka) alluvial-fan surface. We document evidence of three surface-faulting earthquakes based on packages of scarp-derived colluvium that postdate the alluvial-fan units. Bayesian modeling of radiocarbon and luminescence ages yields earthquake times of ca. 9.9 ka, ca. 7.1 ka, and ca. 4.6 ka, forming the longest, most complete paleoseismic record of the Teton fault. We integrate these data with a displaced deglacial surface 4 km NE at Granite Canyon to calculate a postglacial to mid-Holocene (14.4–4.6 ka) slip rate of ∼1.1 mm/yr. Our analysis also suggests that the postglacial to early Holocene (14.4–9.9 ka) slip rate exceeds the Holocene (9.9–4.6 ka) rate by a factor of ∼2 (maximum of 3); however, a uniform rate for the fault is possible considering the 95% slip-rate errors. The ∼5 k.y. elapsed time since the last rupture of the southernmost Teton fault implies a current slip deficit of ∼4–5 m, which is possibly explained by spatially/temporally incomplete paleoseismic data, irregular earthquake recurrence, and/or variable per-event displacement. Our study emphasizes the importance of minimizing slip-rate uncertainties by integrating paleoseismic and geomorphic data sets and capturing multiple earthquake cycles.

Four Major Holocene Earthquakes on the Reelfoot Fault Recorded by Sackungen in the New Madrid Seismic Zone, USA - Gold, Ryan D.; DuRoss, Christopher B.; Delano, Jaime E.; Jibson, Randall W.; Briggs, Richard W.; Mahan, Shannon A.; Williams, Robert A.; Corbett, D. Reide (Journal of Geophysical Research: Solid Earth, 2019)
Three sequences of well‐documented, major ~M7+ earthquakes (1811–1812, ~1450, and ~900 CE) in the New Madrid seismic zone, USA, contribute significantly to seismic hazard in the region. However, it is unknown whether this <550‐year recurrence interval has been constant throughout the Holocene given limited geomorphic evidence of prior earthquakes. We extend the record of paleoearthquakes along the Reelfoot fault via investigation of ridgetop gravitational failure features, interpreted as sackungen. The sackungen occur in bluffs along the eastern margin of the Mississippi River floodplain and are concentrated near (<15 km) the southwest dipping Reelfoot reverse fault. A paleoseismic trench excavated across sackungen at the Paw Paw site exposed four packages of colluvial sediment that postdate 30‐ to 11‐ka Peoria Loess. We interpret the colluvial packages to have been deposited following episodic failure of the sackungen as a result of strong ground motions from the following sequence of earthquakes: event 4, 1640 ± 1730 BCE; event 3, 270 ± 670 CE; event 2, 1430 ± 380 CE; and event 1, 1810 ± 50 CE (2 sigma). Event timing corresponds to previously documented earthquakes and represents the longest archive of paleoearthquakes on the Reelfoot fault. If the trenched sackungen record all major Reelfoot fault earthquakes, our observations in combination with prior investigations indicate a period of quiescence from at least 11 to 4.4 ka, followed by four major seismic events culminating in the 1811–1812 CE sequence. This clustered earthquake recurrence pattern helps place bounds on seismic hazard and geodynamic models in the New Madrid seismic zone.

Combining Conflicting Bayesian Models to Develop Paleoseismic Records: An Example from the Wasatch Fault Zone, Utah - DuRoss, Christopher B.; Bennett, Scott E. K.; Briggs, Richard W.; Personius, Stephen F.; Gold, Ryan D.; Reitman, Nadine G.; Hiscock, Adam I.; Mahan, Shannon A. (Bulletin of the Seismological Society of America, 2018)
Bayesian statistical analyses of paleoseismic data result in the probabilistic determination of earthquake times using geochronological data evaluated in the context of a stratigraphic model. However, a fundamental problem in paleoseismology is how to use the Bayesian approach to model sparse and/or conflicting geochronological datasets, such as those derived from sites exhibiting episodic sedimentary and pedogenic processes in moderate‐ to high‐energy environments (e.g., a normal‐faulted alluvial fan). Using paleoseismic data for the Corner Canyon site on the Salt Lake City segment of the Wasatch fault zone (Utah), we develop an approach by which multiple Bayesian models are combined to generate an earthquake history at a site. This approach accommodates mutually exclusive interpretations of the geochronological data and thereby limits the influence of sparse data, stratigraphically inconsistent ages, or a single, subjective model interpretation. For the Corner Canyon site, we integrate four OxCal Bayesian models to generate a chronology of six events between ∼4.8 and ∼0.5  ka. Late Holocene (post‐5 ka) mean recurrence and vertical slip‐rate estimates are ∼0.9  ky (0.7–1.0 ky; 95% confidence) and 1.1  mm/yr (0.8–1.7  mm/yr range), respectively. Although our method increases the uncertainty in the timing of individual earthquakes, it more objectively accounts for potential geochronological errors and different interpretations of stratigraphic age control. By relaxing the need to select a single age model, our approach yields more accurate earthquake‐timing results that will better facilitate evaluations of along‐fault event correlation and earthquake rupture length.

Unusually large tsunamis frequent a currently creeping part of the Aleutian megathrust - Witter, Robert C.; Carver, Gary A.; Briggs, Richard W.; Gelfenbaum, Guy; Koehler, Richard D.; La Selle, SeanPaul; Bender, Adrian M.; Engelhart, Simon E.; Hemphill-Haley, Eileen; Hill, Troy D. (Geophysical Research Letters, 2016)
Current models used to assess earthquake and tsunami hazards are inadequate where creep dominates a subduction megathrust. Here we report geological evidence for large tsunamis, occurring on average every 300–340 years, near the source areas of the 1946 and 1957 Aleutian tsunamis. These areas bookend a postulated seismic gap over 200 km long where modern geodetic measurements indicate that the megathrust is currently creeping. At Sedanka Island, evidence for large tsunamis includes six sand sheets that blanket a lowland facing the Pacific Ocean, rise to 15 m above mean sea level, contain marine diatoms, cap terraces, adjoin evidence for scour, and date from the past 1700 years. The youngest sheet and modern drift logs found as far as 800 m inland and >18 m elevation likely record the 1957 tsunami. Previously unrecognized tsunami sources coexist with a presently creeping megathrust along this part of the Aleutian Subduction Zone.

Uplift and subsidence reveal a nonpersistent megathrust rupture boundary (Sitkinak Island, Alaska) - Briggs, Richard W.; Engelhart, Simon E.; Nelson, Alan R.; Dura, Tina; Kemp, Andrew C.; Haeussler, Peter J.; Corbett, D. Reide; Angster, Stephen J.; Bradley, Lee-Ann (Geophysical Research Letters, 2014)
We report stratigraphic evidence of land-level change and tsunami inundation along the Alaska-Aleutian megathrust during prehistoric and historical earthquakes west of Kodiak Island. On Sitkinak Island, cores and tidal outcrops fringing a lagoon reveal five sharp lithologic contacts that record coseismic land-level change. Radiocarbon dates, 137Cs profiles, computerized tomography scans, and microfossil assemblages are consistent with rapid uplift circa 290–0, 520–300, and 1050–790 cal yr B.P. and subsidence in A.D. 1964 and circa 640–510 cal yr B.P. Radiocarbon, 137Cs, and 210Pb ages bracketing a sand bed traced 1.5 km inland and evidence for sudden uplift are consistent with Russian accounts of an earthquake and tsunami in A.D. 1788. The mixed uplift and subsidence record suggests that Sitkinak Island sits above a nonpersistent boundary near the southwestern limit of the A.D. 1964 Mw 9.2 megathrust rupture.